2023
DOI: 10.3390/microorganisms11122834
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Sequencing Assessment of Bacterial Pathogens and Associated Antibiotic Resistance Genes in Environmental Samples

Andrei Lobiuc,
Naomi-Eunicia Pavăl,
Mihai Dimian
et al.

Abstract: As seen in earlier and present pandemics, monitoring pathogens in the environment can offer multiple insights on their spread, evolution, and even future outbreaks. The present paper assesses the opportunity to detect microbial pathogens and associated antibiotic resistance genes, in relation to specific pathogen sources, by using nanopore sequencing in municipal waters and wastewaters in Romania. The main results indicated that waters collecting effluents from a meat processing facility exhibit altered commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Although there have been discussions on the nomenclature changes and new genera described, there is a consensus that the Arcobacteraceae family is justified [92,93]. Arcobacteraceae strains have been isolated from diverse habitats including terrestrial, aquatic, animal, food, and human [92][93][94][95][96]. The presence of antimicrobial resistance genes has been documented in strains of Arcobacteraceae [94].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been discussions on the nomenclature changes and new genera described, there is a consensus that the Arcobacteraceae family is justified [92,93]. Arcobacteraceae strains have been isolated from diverse habitats including terrestrial, aquatic, animal, food, and human [92][93][94][95][96]. The presence of antimicrobial resistance genes has been documented in strains of Arcobacteraceae [94].…”
Section: Discussionmentioning
confidence: 99%
“…Arcobacteraceae strains have been isolated from diverse habitats including terrestrial, aquatic, animal, food, and human [92][93][94][95][96]. The presence of antimicrobial resistance genes has been documented in strains of Arcobacteraceae [94]. Antimicrobials such as triclocarban that occur with anthropogenic reactive nitrogen sources in the environment can affect the efficiency of denitrification [91].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research reported the applications of the nanopore sequencing method on various pathogens of human beings. However, this method was also effective in the pathogenic diagnostics of plants, animals, and environmental samples [26,[45][46][47]. For example, different phytopathogenic and endophytic fungi such as Cladosporium, Didymosphaeria, Paraconiothyrium, Penicillium, Phoma, and Verticillium species were detected in the olive tree using ONT sequencing for three DNA loci of ITS, betatubulin, and 28S LSU regions [48].…”
Section: Nanopore Sequencing Technology In Pathogenic Diagnosticsmentioning
confidence: 99%
“…The pathogens are not only found in the host but also the environment. Therefore, the detection of pathogens in different environments such as soil, river, water, and air samples was conducted using ONT [45,[52][53][54][55]. The nanopore sequencing method was also successfully applied for the detection of antibiotic resistance genes in microbes [45,53].…”
Section: Nanopore Sequencing Technology In Pathogenic Diagnosticsmentioning
confidence: 99%
“…Several studies have shown that GeneXpert MTB/RIF is less accurate than gene sequencing methods (such as nanopore sequencing) for the diagnosis of PTB [ 12 14 ]. Nanopore sequencing is a new generation of gene sequencing technology, which is characterized by fast sequencing speed, long sequencing reads, real-time monitoring of sequencing data, and portable equipment [ 15 ]. So far, nanopore sequencing is relatively expensive compared to other tests and requires good laboratory conditions, but these are not worth mentioning compared to its benefits [ 16 ].…”
Section: Introductionmentioning
confidence: 99%